Pelaksanaan Relationship Marketing dan Corporate Social Responsibility Dalam Upaya Meningkatkan Loyalitas Pelanggan Indosat - Sri Anik; Andina Juhara (Forum Manajemen Indonesia (FMI), 2014)
Come at the global marketing requires companies to be more creative and be more observant in serving customers to achieve high sustainable business (sustainability), so it takes efforts beyond than just improve the quality and production of goods / services. Services and provision of value-added are the key words of modern marketing, and implementation of relationship marketing and corporate social responsibility will be influential in increasing customer loyalty. This study used a sample of 100 respondents Indosat customers. Analysis of the data used : test the quality of data, test of classical assumption, multiple linear regression analysis, and test of hypothesis with t test and coefficient of determination. Results with test of multiple linear regression showed relationship marketing variables into the biggest variables that affect customer loyalty, with the value of 0.677 and Corporate Social Responsibility variable has a value of 0.280. From the test results obtained by the adjusted coefficient of determination R2 of 72.3%. This suggests that 72,3% variation of customer loyalties explained by the model, while the rest 27,7% explained by variables outside the model. Keywords : Relationship Marketing, Corporate Social Responsibility, Customer loyalty.